2012
DOI: 10.1093/hmg/dds142
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy for Synaptojanin1 in Down syndrome is functionally linked to the enlargement of early endosomes

Abstract: Enlarged early endosomes have been observed in neurons and fibroblasts in Down syndrome (DS). These endosome abnormalities have been implicated in the early development of Alzheimer's disease (AD) pathology in these subjects. Here, we show the presence of enlarged endosomes in blood mononuclear cells and lymphoblastoid cell lines (LCLs) from individuals with DS using immunofluorescence and confocal microscopy. Genotype-phenotype correlations in LCLs carrying partial trisomies 21 revealed that triplication of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 61 publications
5
89
0
Order By: Relevance
“…More importantly, increased synj1 expression has been functionally linked to the enlargement of early endosomes (46). It has been reported that endosome anomalies are the earliest specific pathology reported in AD brain tissue (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, increased synj1 expression has been functionally linked to the enlargement of early endosomes (46). It has been reported that endosome anomalies are the earliest specific pathology reported in AD brain tissue (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in the dose of the chromosome 21 gene cystatin B (CSTB), which encodes an endogenous inhibitor of lysosomal cathepsins, decreases the accumulation of Aβ and associated cognitive deficits 147 . Overexpression of another chromosome 21 gene, synaptojanin 1 (SYNJ1), which encodes a phosphoinositide phosphatase that regulates levels of membrane phosphatidylinositol-4,5-bisphosphate, has been associated with endosomal enlargement 148 , whereas reduced expression of SYNJ1 lowers Aβ accumulation, as well as neuronal dysfunction and cognitive deficits 149,150 . How endosomal enlargement caused by trisomy contributes to neuronal dysfunction and degeneration is another important area for future research.…”
Section: Disruption Of Secretory and Endosomal Systemsmentioning
confidence: 99%
“…For example, ubiquitin-specific peptidase 16 (USP16) or DYRK1A upregulation alters stem cell fate [167][168][169] , which may in turn alter neuronal differentiation. Additionally, overexpression of several chromosome 21 genes (for example, the microRNA gene mir-155 and the protein-coding genes SYNJ1, regulator of calcineurin 1 (RCAN1), intersectin 1 (ITSN1) and DS cell adhesion molecule (DSCAM)) has been implicated in deficits in synaptic structure and function 148,170,171 . These genes may also play a part in AD-DS, perhaps via an effect on APP processing or on cognitive reserve.…”
Section: Neuronal Development and Functionmentioning
confidence: 99%
“…It has been associated with the development of neuronal diseases in mice and humans (30,53). Its role and expression in T cells has heretofore not been reported.…”
Section: Figurementioning
confidence: 99%